Answer:
it is 46
Explanation:
First you need to solve.. So put 3x - 10 and 2x + 1 together as one equation.
It should look like this:
3x - 10 = 2x + 1
Now you just need to solve it.
1) First you add 10 on both sides.
3x - 10 = 2x + 1
+ 10 = + 10
------------------------
3x = 2x + 11
2) Then you subtract 2x on both sides.
3x = 2x + 11
- 2x =- 2x + 11
-------------------------
x = 11
3) Now you plug in 11 for x.
3x - 10 = 2x + 1
Like this:
3(11) - 10 = 2(11) + 1
33 - 10 = 22 + 1
23 =23
So C to E and E to A = 23
To get from C to A just add 23 + 23 which is 46. And that is ur answer.
you can slove this in this way if want more explansion ask me